ACCOUNTING IN THE NEWS PRINT INDUSTRY. - Ware, G. A. (The Accounting Review, 1926)
Abstract The interest in uniform accounting or standard accounting in the newsprint industry began to become manifest about ten years ago. In 1916 a firm of public accountants issued a report on the subject. And since that time fairly rapid progress has been made. The movement was greatly facilitated by the attitude that the Governments of the United States and Canada took regarding the cost of manufacturing and price, when the industry was controlled during the war. They insisted that definite costs should be arrived at and this greatly promoted accounting activities in the industry, so that much of the resistance to the development of uniform cost accounting, which has been found in other industries, was overcome in this way in the news print industry. Accountants were employed both by the Government and by the manufacturers to make extensive investigations of costs and related matters and these investigations disclosed the lack of reliable cost data and indicated the necessity for development.